Sub (x+1) for x
f(x+1)=2(x+1)^2+3
f(x+1)=2(x^2+2x+1)+3
f(x+1)=2x^2+4x+2+3
f(x+1)=2x^2+4x+5
D is answer
Answer:
B) {-8,-2,3,4,7,11}
Step-by-step explanation:
range is y
Answer:
x = 6
y = 4
Step-by-step explanation:
Let the two numbers be x and y
<u><em>Condition 1:</em></u>
7x+3y = 54 -----------(1)
<u><em>Condition 2:</em></u>
x = 2+y -----------------(2)
<em>Putting (2) in (1)</em>
=> 7(y+2)+3y = 54
=> 7y+14+3y = 54
=> 10y = 54-14
=> 10y = 40
<em>Dividing both sides by 10</em>
=> y = 4
<em>Now putting y = 4 in eq(2)</em>
=> x = 2+4
=> x = 6
Answer:
0.5y+2y
Step-by-step explanation:
bc you divide out the y
![a = \pi \: {r}^{2}](https://tex.z-dn.net/?f=a%20%3D%20%5Cpi%20%5C%3A%20%20%7Br%7D%5E%7B2%7D%20)
![r = \frac{36}{2}](https://tex.z-dn.net/?f=r%20%3D%20%20%5Cfrac%7B36%7D%7B2%7D%20)
Using pi at 3.14 the answer is 1,017.36